The use of e-governance by local authorities to improve service delivery: A case of Chitungwiza Municipality - Patson Tapiwa Matimati; Naome Rajah (Research and Reviews, 2023)
This research was based on assessing the use of e-governance by local authorities to improve service delivery: A case of Chitungwiza Municipality. The research objectives were to find out the benefits of e-governance system, to find out the challenges being faced by Chitungwiza Municipality in implementation and use of e-governance system and to proffer possible strategies that can be employed to ameliorate some of the challenges being faced. The research was confined to Chitungwiza respondents only. Literature review then focused on giving description of e-governance, benefits of e-governance, challenges being faced by the local authorities in using e-governance, strategies that can be adopted by local authorities to implement and use e-governance and the use of e-governance system by other local authorities in different countries. Descriptive research design was used. Stratified random sampling technique was used to select the respondents. The sample for the research was 50 respondents which constituted 10 employees, 10 top management and 30 residents. Questionnaires and personal interviews were used as the research instruments. An overall response rate of 84% was obtained from the questionnaires and interviews. Data presentation and analysis was done. Findings obtained from the research study were presented in tables, graphs and pie-charts followed by the analysis. Major findings of the research were that, Chitungwiza Municipality is faced with financial shortages, lack of adequate machinery and minimum support from the government so as to fully implement and use e-governance system to improve service delivery. The council does not have its website where people can access information. Some of the council departments do not have adequate computers and some no longer function well. People have limited knowledge on e-governance and they do not have adequate knowledge on the benefits of using e-governance system. Strategies that can be adopted by Chitungwiza Municipality to implement and use e-governance include engaging public private partnerships, training of personnel, increasing awareness to the public on e-governance, and city twinning. Lastly recommendations were made which include, efforts should be made to ensure that e-governance system is taken aboard by the Municipality in years to come in order to improve service delivery to the public through advanced use of internet and council website, the council need to plan and have a council website so as to make services accessible to the citizens ,training of staff should be done so that they can gain deep understanding on the benefits of e-governance and the council should make use of public private partnerships and city twinning so as to acquire financial and other resources in order to implement and use e-governance system to improve service delivery